Contamination by canine gastrointestinal parasites in eighteen beaches of Central Pacific Costa Rica: public health implications (Ciencias Veterinarias, 2013)
The purpose of this study was to evaluate contamination by gastrointestinal parasites (GIP) in 18 beaches ofCentral Pacific Costa Rica through the analysis of canine fecal samples, in order to evidence the possible zoonoticinfection of visitors. Of the 18 beaches studied during December 2008 and February of 2009, 16 (88.9%)had canine fecal samples. Despite the presence of animals in Caldera and Tárcoles, no fecal samples werefound, while a great quantity of samples (53) was collected in Puntarenas. A total of 191 canine fecal sampleswere collected, of which 115 (60.2%) presented GIP identified as Ancylostomatidae (84.3%), Trichuris vulpis(24.3%), Dipylidium caninum (11.3%), Toxocara canis (6.9%) and Coccidia (6.1%). The prevalence of the GIPin the beaches was: Ancylostomatidae (49.7%), Tr. vulpis (15.2%), D. caninum (7.3%), T. canis and coccidian(3.7%, respectively). With respect to zoonotic parasites, Ancylostomatidae and T. canis were found in 15 (93.8%) and 4 (25.0%) beaches, respectively. During the process of collecting samples on the beaches, the presence of both owned dogs and strays was observed. Results obtained in this study show the role of the veterinarian in the promotion of animal, public and environmental health.